Mutations in HISTONE ACETYLTRANSFERASE1 affect sugar response and gene expression in Arabidopsis - Heisel, Timothy J.; Li, Chun Yao; Grey, Katia M.; Gibson, Susan I. (Frontiers in Plant Science, 2013)
Nutrient response networks are likely to have been among the first response networks to evolve, as the ability to sense and respond to the levels of available nutrients is critical for all organisms. Although several forward genetic screens have been successful in identifying components of plant sugar-response networks, many components remain to be identified. Towards this end, a reverse genetic screen was conducted in Arabidopsis thaliana to identify additional components of sugar-response networks. This screen was based on the rationale that some of the genes involved in sugar-response networks are likely to be themselves sugar regulated at the steady-state mRNA level and to encode proteins with activities commonly associated with response networks. This rationale was validated by the identification of hac1 mutants that are defective in sugar response. HAC1 encodes a histone acetyltransferase. Histone acetyltransferases increase transcription of specific genes by acetylating histones associated with those genes. Mutations in HAC1 also cause reduced fertility, a moderate degree of resistance to paclobutrazol and altered transcript levels of specific genes. Previous research has shown that hac1 mutants exhibit delayed flowering. The sugar-response and fertility defects of hac1 mutants may be partially explained by decreased expression of AtPV42a and AtPV42b, which are putative components of plant SnRK1 complexes. SnRK1 complexes have been shown to function as central regulators of plant nutrient and energy status. Involvement of a histone acetyltransferase in sugar response provides a possible mechanism whereby nutritional status could exert long-term effects on plant development and metabolism.